Strength, power and speed characteristics in elite academy soccer. - Sherwood, C. N.; Read, P.; Till, K.; Paxton, K.; Keenan, J.; Turner, A. N. (Journal of Australian Strength and Conditioning, 2021)
The purpose of this study was 1) to present the strength, speed and power characteristics of elite youth soccer players and provide benchmark data for strength and conditioning coaches; 2) to compare the speed, strength and power characteristics of youth soccer players by competition structure age categories; and 3) to determine the relationships between lower-body strength, eccentric hamstring strength, upper-body strength, sprint and jump performance. Sixty-four (n = 64) academy male soccer players (U16s n = 18, U18s n = 22, and U23s n = 24), performed a predicted maximal squat test, bench press test and prone row test, eccentric hamstring strength test, countermovement jump, and 10m and 20m sprint speed test. The analysis of variance showed that age category had a significant effect on height, mass, countermovement jump, left eccentric hamstring strength, right eccentric hamstring strength, average eccentric hamstring strength, 20m sprint speed, estimated one repetition maximum squat absolute and relative, and estimated one repetition maximum bench press absolute. In the U16s age group, there was a significant relationship between 10m sprint and absolute squat strength (r = -0.759), and 20m sprint speed and absolute squat strength (r = -0.757). In the U23s age group, there was a significant relationship with 10m sprint speed and relative squat strength (r = -0.598), and 20m sprint speed and relative squat strength (r = -0.653). This study provides comparative data for elite academy soccer players. The benchmarks, allow strength and conditioning coaches to be individualised in their approach to training by creating subgroups.